Empowering an Eco-Conscious Generation: Exciting Introduction to Ecoenzyme-Based Halal Detergents - Linda Lisdiana; Neneng Windayani; Ai Mae; Riduan Zain (TAAWUN, 2025)
This research aims to introduce the younger generation to sustainable practices through a Service Learning project at SMPN 1 Tanjungsari. The methods used by Service Learning include learning, workshops, waste fermentation practices, eco-enzyme detergent production, as well as community education and reflection to improve students' holistic learning and environmental awareness. The project involved 30 science club students who were taught to make ecoenzyme-based halal detergents from organic waste. Ecoenzyme, the fermentation of organic waste, is an eco-friendly alternative to chemical detergents that damage ecosystems and human health. Through a series of lectures, workshops, and practical activities, students learned about the fermentation process, product formulation, and the importance of halal certification. The project results showed significant improvements in students' environmental awareness and practical skills, effective and biodegradable detergent formulations, and positive impacts on the community through awareness campaigns and organic waste reduction. The project emphasized the importance of practical and culturally relevant environmental education to form sustainable habits among the younger generation.